Inclisiran and cardiovascular events: a patient-level analysis of phase III trials. (4th November 2022) - Ray, Kausik K; Raal, Frederick J; Kallend, David G; Jaros, Mark J; Koenig, Wolfgang; Leiter, Lawrence A; Landmesser, Ulf; Schwartz, Gregory G; Lawrence, David; Friedman, Andrew; Garcia Conde, Lorena; Wright, R Scott; et al.
Abstract: Background: Inclisiran, an siRNA administered twice-yearly, significantly reduced LDL cholesterol (LDL-C) in Phase III trials. Whether lowering LDL-C with inclisiran translates into a lower risk of cardiovascular (CV) events is not yet established. Methods and results: Patient-level, pooled analysis of ORION-9, −10 and −11, included patients with heterozygous familial hypercholesterolaemia, atherosclerotic CV disease (ASCVD), or ASCVD risk equivalent on maximally tolerated statin-therapy, randomized 1:1 to receive 284 mg inclisiran or placebo on Days 1, 90, and 6-monthly thereafter for 18 months. Prespecified exploratory endpoint of major cardiovascular events (MACEs) included non-adjudicated CV death, cardiac arrest, non-fatal myocardial infarction (MI), and fatal and non-fatal stroke, evaluated as part of safety assessments using a standard Medical Dictionary for Regulatory Activities basket. Although not prespecified, total fatal and non-fatal MI, and stroke were also evaluated. Mean LDL-C at baseline was 2.88 mmol/L. At Day 90, the placebo-corrected percentage reduction in LDL-C with inclisiran was 50.6%, corresponding to an absolute reduction of 1.37 mmol/L (both P < 0.0001). Among 3655 patients over 18 months, 303 (8.3%) experienced MACE, including 74 (2.0%) fatal and non-fatal MIs, and 28 (0.8%) fatal and non-fatal strokes. Inclisiran significantly reduced composite MACE [OR (95% CI): 0.74 (0.58–0.94)], but not fatal and non-fatal MIs [OR (95% CI): 0.80 (0.50–1.27)] or fatal and non-fatal stroke [OR (95% CI): 0.86 (0.41–1.81)]. Conclusion: This analysis offers early insights into the potential CV benefits of lowering LDL-C with inclisiran and suggests potential benefits for MACE reduction. These findings await confirmation in the larger CV outcomes trials of longer duration. Abstract : Exploratory findings from a patient-level, pooled analysis of the pivotal Phase III ORION trials (−9, −10, and −11) suggest that treatment with a 6 monthly dosing schedule of inclisiran (after the initial and three-month doses) over 18 months is associated with reductions in the composite endpoint of major cardiovascular events. Structured Graphical Abstract: Structured Graphical Abstract AE, adverse event; HR, hazard ratio; LDL-C, low-density lipoprotein cholesterol; mRNA, messenger ribonucleic acid; OR, odds ratio; PCSK9, proprotein convertase subtilisin/kexin type 9; siRNA, small interfering ribonucleic acid.